Screening for early warning of psychological crisis and intervention in children aged 8–18 years with cancer: a historical controlled trial - Yu, Lu; Mo, Lin; Liu, Yixuan; Huang, Xiaoyan (Frontiers in Pediatrics, 2023)
Background Childhood cancer is becoming an emerging healthcare issue in mainland China. Extensive evidence in the literature has demonstrated that cancer and its treatment experience can cause psychological distress that can lead to developmental problems in children with cancer. This study aims to screen for early warning of psychological crisis in children aged 8–18 years with cancer, establish a model of early warning intervention for children with cancer, and explore its application effects. Methods We recruited 345 children with cancer and aged 8–18 years as the study participants, of whom 173 children were selected as historical controls during the period between December 2019 and March 2020 and 172 children were selected as the intervention group during the period between July 2020 and October 2020. The routine nursing model was adopted for the control group, and the early warning and intervention model was applied for the intervention group. The early warning and intervention model consisted of four stages: (1) establishing a management team to assess the risk of psychological crisis, (2) developing a three-level early warning response mechanism, (3) developing specific response plans, and (4) creating an evaluation summary and optimization mode. The DASS-21 was used to evaluate the psychological status of children with cancer before and 3 months after the intervention. Results The average age of the control group was 11.43 ± 2.39 years, with 58.96% boys and 61.27% diagnosed with leukemia. The average age of the intervention group was 11.62 ± 2.31 years, with 58.72% boys and 61.63% diagnosed with leukemia. There was a significant reduction in depressive symptoms (4.91 ± 3.98, t = 12.144, P < 0.05), anxiety symptoms (5.79 ± 4.34, t = 8.098, P < 0.05), and stress symptoms (6.98 ± 4.67, t = 11.22, P < 0.05) in the intervention group. The incidence rates of depression, anxiety, and stress were significantly lower in the intervention group (12.79%, 29.07%, and 5.23%, respectively) than in the control group (46.82%, 49.71%, and 27.17%, respectively) (all P's < 0.05). Conclusions Our study suggests that the early detection and timely management of psychological symptoms through a nursing intervention model can effectively reduce depressive, anxiety, and stress symptoms in Chinese children with cancer. Future work should include conducting qualitative interviews to understand the psychological experiences of children with cancer throughout their entire life cycle.